Pengembangan Game Edukasi “Aksara Swara” sebagai Media Pembelajaran Huruf Vokal Aksara Jawa Berbasis Construct 3 - Muhammad Syahrul Falah; Muhammad Muzaki Maruf; Faza Afwan Nugroho (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Learning Javanese script still faces various challenges, particularly the low interest and understanding of students due to the limited use of interactive learning media. Javanese script is often considered difficult because of its diverse character forms and its limited use in daily life. Therefore, alternative learning media that are more interactive and engaging are needed. This study aims to develop an educational game entitled “Aksara Swara” as an interactive learning medium for introducing Javanese vowel characters. This research employs a Research and Development (R&D) method using the Four-D development model (Define, Design, Develop, Disseminate). The game was developed using Construct 3 with a quiz-based concept and different levels of difficulty. Product testing was conducted using functional testing (black box testing) to ensure that all game features functioned properly according to the design. The results indicate that the “Aksara Swara” game functions well, has an easy-to-understand gameplay mechanism, and is able to present Javanese script learning materials interactively. Therefore, the educational game “Aksara Swara” can be used as an alternative learning medium to support the introduction of Javanese script in an enjoyable way.